Remanufacturing mode and strategic decision: a game-theoretic approach - Zhou, Qin (2023)
This study considers a supply chain consisting of an original equipment manufacturer (OEM) and a contract manufacturer (CM). The OEM outsources the production of new products to the CM and cooperates with the CM again in remanufacturing. However, the cooperation in remanufacturing may be either through outsourcing or authorization. As the remanufacturer, the CM may choose among three remanufacturing strategies (i.e., not remanufacturing, partial remanufacturing, and full remanufacturing) based on the quality of the collected products. We examined the CM's optimal remanufacturing strategy decision for a given remanufacturing mode (i.e., outsourcing or authorization), the OEM's remanufacturing mode decision when the CM's remanufacturing strategy has been determined, and the environmental impact of the two remanufacturing modes. The results show that, depending on the profitability of new and remanufactured products, the CM will adopt different remanufacturing strategies in the two remanufacturing modes, and not remanufacturing may become an optimal choice for the CM in the authorization mode. For the OEM, both remanufacturing modes can give the OEM a higher profit when certain market conditions are reached, whereas the CM's profit in the outsourcing mode is always larger than that in the authorization mode. As such, outsourcing can become a win-win solution for the OEM and CM. Both remanufacturing modes can achieve the best possible environmental outcome when the full remanufacturing strategy is adopted. However, outsourcing remanufacturing is always more environmentally friendly than the authorization mode in the partial remanufacturing scenario.